Cardiovascular system diseases in children with chronic kidney diseases: Epidemiology, risk factors, pathogenesis - M. E. Aksenova (Rossijskij Vestnik Perinatologii i Pediatrii, 2016)
Cardiovascular disease is a common complication of chronic kidney diseases and a leading cause of death in patients with end-stage renal failure. Involvement of the cardiovascular system in chronic kidney disease is due to the early formation of traditional factors (hypertension, dyslipidemia) and the presence of kidney disease-related cardiovascular risk factors (anemia, dysproteinemia, and calcium and phosphorus metabolic disturbances). The kidney disease-related risk factors are determined by the nature of kidney disease and the degree of renal dysfunction. The cardiovascular changes include remodeling of the vascular wall and myocardium, leading to their dysfunctions with time. The article considers the current views on the pathogenesis of cardiovascular diseases in patients with chronic kidney disease.